Outbreak of Salmonella Typhimurium ST19 linked to passerine birds and cats in Norway, March to July 2024 - Hilde Marie Lund; Lin T. Brandal; Liz Ertzeid Ødeskaug; Heidi Lange; Polina Katsiouleri; Gro S. Johannessen; Bjarne Bergsjø; Åsne Sangolt; Rikard Dryselius; Nadja Karamehmedovic; Henry Kuronen; Anni Vainio; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose In June 2024, a genomic cluster of seven Salmonella Typhimurium - sequence type 19, and cluster type 21092 - was detected in Norway, triggering a national outbreak investigation. Methods Information about new cases was collected from the Norwegian Surveillance System for Communicable Diseases and the database at the National Reference Laboratory for Enteropathogenic Bacteria (NRL) at the Norwegian Institute of Public Health (NIPH). Microbiological analyses were conducted by NRL at NIPH for human samples and at the Norwegian Veterinary Institute for animal samples. Epidemiological data was collected through interviews. International notification was sent via EpiPulse. Results Eleven cases in total, sampled between March 6 and July 11, 2024, were identified across Norway. The median age of affected individuals was three years. Notably, 73% of the cases reported prior contact with cats or passerine birds. The outbreak strain was also detected in a faecal sample from a cat belonging to one of the affected households, suggesting an animal source. Concurrently, Finland and Sweden reported five and six cases, respectively, involving the same outbreak strain. Several of these individuals also reported contact with cats or birds. Conclusions Passerine birds are a well-documented reservoir for S. Typhimurium in the Nordic region, often leading to transmission to both cats and humans. This outbreak highlights the role of animal exposure in the spread of S. Typhimurium and emphasize the need for timely, targeted public health communication on infection prevention measures.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Beyond temperature: predictive modelling of range shifts in benthic peracarids across the northern North Pacific under future climate scenarios - Stefanie Kaiser; Anna M. Jażdżewska; Sarah Gerken; Anne Helene S. Tandberg; Chih-Lin Wei; Davide Di Franco; Hanieh Saeedi; Hannah Owens; Henry Knauber; Emma Palacios Theil; Angelika Brandt; Pedro Martinez Arbizu; et al. (Progress in Oceanography, 2026)

Age-dependent cementitious leachate effects on metal and radionuclide sorption to sediments from a subsurface waste-disposal site - Peng Lin; Karah Greene; Wei Xing; Steven Simner; Christina Logan; Richard Henry; Daniel I. Kaplan (Applied Geochemistry, 2026)

Genetic mapping of novel QTL for seed protein stability in food-grade soybean (Glycine max) - Andrew A. Mitchell; Feng Lin; Heng Ye; Tri Vuong; Zixiang Wen; Biructawit Tessema; Randall Laurenz; Raju Thada Magar; Henry T. Nguyen; Dechun Wang (Theoretical and Applied Genetics, 2025)
Key message Two novel quantitative trait loci associated with soybean protein content stability were identified on chromosomes 10 and 18. Haplotype analysis showed these to significantly improve stability without protein content penalty. Abstract Soybean seed protein content is a complex physiological trait under polygenic control and significant genotype by environment interaction. Protein content is largely influenced by ambient atmospheric temperature at pod-filling, with increased temperatures enhancing seed protein accumulation. The identification of genomic regions associated with protein content stability will facilitate an increased understanding of seed development physiology and assist in the development of more broadly adapted food-grade soybean cultivars. In this work, 210 recombinant inbred lines were derived from the intraspecific cross of the high protein accession BARC - 6 (PI 555396), and the low protein MSU breeding accession E14077 for the investigation of quantitative trait loci associated with protein content and protein content stability across multiple years and test locations. Indices for static protein content stability were used to estimate genome by environment interactions across Northern and Southern soybean production regions. Composite interval mapping returned one stable major effect QTL associated with protein content on chromosome 20 explaining approximately 20.7% of phenotypic variation. Two novel QTLs associated with absolute protein stability were detected on chromosomes 10 and 18, explaining approximately 8.6% and 7.6% of phenotypic variation, respectively. SNP-based haplotype analysis showed simultaneous favorable effects on protein content and stability when desirable alleles for these QTL were pyramided. These results will serve as a valuable tool for the molecular breeding of food-grade soybean cultivars harboring elevated protein content coupled with improved stability across varied environments, thus addressing a key challenge in meeting the global rise in soybean protein demand for both livestock feed and human consumption.

Correction: The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

International research initiative on genomics-guided sugarcane breeding - Xingtan Zhang; Jungang Wang; Noor-ul-Áin; Youxiong Que; Jisen Zhang; Javeria Abid; Peifang Zhao; Yuebin Zhang; Jishan Lin; Li-yu Chen; Yixue Bao; Robert Henry; et al. (Molecular Plant, 2025)

Predicting 30-day reoperation following primary total knee arthroplasty: machine learning model outperforms the ACS risk calculator - Tony Lin-Wei Chen; Anirudh Buddhiraju; Blake M. Bacevich; Henry Hojoon Seo; Michelle Riyo Shimizu; Young-Min Kwon (Medical & Biological Engineering & Computing, 2025)

QTL mapping and whole-genome sequencing analysis for novel genetic resources associated with sucrose content in soybean [Glycine max (L.) Merr.] - Dongho Lee; Tri D. Vuong; James G. Shannon; Qijian Song; Feng Lin; Henry T. Nguyen (Theoretical and Applied Genetics, 2025)
Key message A major QTL for sucrose content was mapped on chromosome 8 in PI 506593. The novel genetic variants and candidate genes were further identified within the major QTL. Abstract Sucrose in soybean [ Glycine max (L.) Merr.] contribute to animal feed efficiency and natural sweetness of soy products. Thus, identifying novel genetic resources, such as quantitative trait loci (QTL), associated with sucrose content in soybean is essential for enhancing seed values. In this study, two recombinant inbred line populations derived from the same high sucrose donor parent, PI 506593, were used to identify significant QTLs. A total of 11 sucrose-related regions on chromosomes (Chrs.) 4, 5, 6, 8, 10, and 13 were identified using QTL analysis. Among them, four QTLs ( qSUC_08.1 , qSUC_08.2 , qSUC_08.3 , and qSUC_08.4 ) were clustered in the interval of 40,597,410–42,861,364 bp on Chr. 8, which was considered major QTL region. A desirable marker at 41,834,095 bp was tested in two populations, showing that two phenotypically extreme groups were efficiently differentiated. We further identified 44 and 54 candidate genes with non-synonymous mutations in the major QTL region based on the annotations of Wm82.a2.v1 and Wm82.a5.v1 assemblies, respectively. Among 54 candidate genes from Wm82.a5.v1, Protein Variation Effect Analyzer (PROVEAN) revealed that 18 genes contained 34 variants that had deleterious impacts on biological functions. RNA-seq analysis highlighted five candidate genes that were highly expressed in pod and seed tissues during reproductive stages and other plant parts. A gene, Gm_Wm82_23219 ( Glyma.08G293800 , Wm82.a2.v1) encoding proline-rich protein 4-like, was highlighted in both PROVEAN and RNA-seq analyses. Novel findings in this study will be valuable genetic resources in soybean breeding programs that aim to improve efficiency in animal feed and human food.

Practical Characterization Strategies for Comparison, Qualification, and Selection of Cell Viability Detection Methods for Cellular Therapeutic Product Development and Manufacturing - Yongyang Huang; Rachel Watkins; Samir Patel; Mackenzie Pierce; Carolina Franco Nitta; Henry Qazi; William L. Rice; Bo Lin; Chris Lowe; Carlos le Sage; Leo Li-Ying Chan (Journal of Fluorescence, 2024)

Generalizability of machine learning models predicting 30-day unplanned readmission after primary total knee arthroplasty using a nationally representative database - Anirudh Buddhiraju; Michelle Riyo Shimizu; Henry Hojoon Seo; Tony Lin-Wei Chen; MohammadAmin RezazadehSaatlou; Ziwei Huang; Young-Min Kwon (Medical & Biological Engineering & Computing, 2024)

Predicting 30-day unplanned hospital readmission after revision total knee arthroplasty: machine learning model analysis of a national patient cohort - Tony Lin-Wei Chen; Michelle Riyo Shimizu; Anirudh Buddhiraju; Henry Hojoon Seo; Murad Abdullah Subih; Shane Fei Chen; Young-Min Kwon (Medical & Biological Engineering & Computing, 2024)

Determinants of microbiome composition: Insights from free‐ranging hybrid zebras ( Equus quagga × grevyi ) - Joel O. Abraham; Bing Lin; Audrey E. Miller; Lucas P. Henry; Margaret Y. Demmel; Rosemary Warungu; Margaret Mwangi; Patrick M. Lobura; Luisa F. Pallares; Julien F. Ayroles; Robert M. Pringle; Daniel I. Rubenstein (Molecular Ecology, 2024)
The composition of mammalian gut microbiomes is highly conserved within species, yet the mechanisms by which microbiome composition is transmitted and maintained within lineages of wild animals remain unclear. Mutually compatible hypotheses exist, including that microbiome fidelity results from inherited dietary habits, shared environmental exposure, morphophysiological filtering and/or maternal effects. Interspecific hybrids are a promising system in which to interrogate the determinants of microbiome composition because hybrids can decouple traits and processes that are otherwise co‐inherited in their parent species. We used a population of free‐living hybrid zebras ( Equus quagga × grevyi ) in Kenya to evaluate the roles of these four mechanisms in regulating microbiome composition. We analysed faecal DNA for both the trn L‐P6 and the 16S rRNA V4 region to characterize the diets and microbiomes of the hybrid zebra and of their parent species, plains zebra ( E. quagga ) and Grevy's zebra ( E. grevyi ). We found that both diet and microbiome composition clustered by species, and that hybrid diets and microbiomes were largely nested within those of the maternal species, plains zebra. Hybrid microbiomes were less variable than those of either parent species where they co‐occurred. Diet and microbiome composition were strongly correlated, although the strength of this correlation varied between species. These patterns are most consistent with the maternal‐effects hypothesis, somewhat consistent with the diet hypothesis, and largely inconsistent with the environmental‐sourcing and morphophysiological‐filtering hypotheses. Maternal transmittance likely operates in conjunction with inherited feeding habits to conserve microbiome composition within species.

Climatic Fluctuation of Marine Isotope Stage 9: A Case Study in the Southern Margin of the Chinese Loess Plateau - Tieniu Wu; Antai Cheng; Henry Lin; Hailin Zhang; Yi Jie (Journal of Earth Science, 2023)

Correction to: Breeding for disease resistance in soybean: a global perspective - Feng Lin; Sushil Satish Chhapekar; Caio Canella Vieira; Marcos Paulo Da Silva; Alejandro Rojas; Dongho Lee; Nianxi Liu; Esteban Mariano Pardo; Yi-Chen Lee; Zhimin Dong; Jose Baldin Pinheiro; Leonardo Daniel Ploper; et al. (Theoretical and Applied Genetics, 2022)

Breeding for disease resistance in soybean: a global perspective - Feng Lin; Sushil Satish Chhapekar; Caio Canella Vieira; Marcos Paulo Da Silva; Alejandro Rojas; Dongho Lee; Nianxi Liu; Esteban Mariano Pardo; Yi-Chen Lee; Zhimin Dong; Jose Baldin Pinheiro; Leonardo Daniel Ploper; et al. (Theoretical and Applied Genetics, 2022)
Key message This review provides a comprehensive atlas of QTLs, genes, and alleles conferring resistance to 28 important diseases in all major soybean production regions in the world. Abstract Breeding disease-resistant soybean [ Glycine max (L.) Merr.] varieties is a common goal for soybean breeding programs to ensure the sustainability and growth of soybean production worldwide. However, due to global climate change, soybean breeders are facing strong challenges to defeat diseases. Marker-assisted selection and genomic selection have been demonstrated to be successful methods in quickly integrating vertical resistance or horizontal resistance into improved soybean varieties, where vertical resistance refers to R genes and major effect QTLs, and horizontal resistance is a combination of major and minor effect genes or QTLs. This review summarized more than 800 resistant loci/alleles and their tightly linked markers for 28 soybean diseases worldwide, caused by nematodes, oomycetes, fungi, bacteria, and viruses. The major breakthroughs in the discovery of disease resistance gene atlas of soybean were also emphasized which include: (1) identification and characterization of vertical resistance genes reside rhg1 and Rhg4 for soybean cyst nematode, and exploration of the underlying regulation mechanisms through copy number variation and (2) map-based cloning and characterization of Rps11 conferring resistance to 80% isolates of Phytophthora sojae across the USA. In this review, we also highlight the validated QTLs in overlapping genomic regions from at least two studies and applied a consistent naming nomenclature for these QTLs. Our review provides a comprehensive summary of important resistant genes/QTLs and can be used as a toolbox for soybean improvement. Finally, the summarized genetic knowledge sheds light on future directions of accelerated soybean breeding and translational genomics studies.

A biallelic variant in CLRN2 causes non-syndromic hearing loss in humans - Barbara Vona; Neda Mazaheri; Sheng-Jia Lin; Lucy A. Dunbar; Reza Maroofian; Hela Azaiez; Kevin T. Booth; Sandrine Vitry; Aboulfazl Rad; Franz Rüschendorf; Pratishtha Varshney; Ben Fowler; et al. (Human Genetics, 2021)
Deafness, the most frequent sensory deficit in humans, is extremely heterogeneous with hundreds of genes involved. Clinical and genetic analyses of an extended consanguineous family with pre-lingual, moderate-to-profound autosomal recessive sensorineural hearing loss, allowed us to identify CLRN2, encoding a tetraspan protein, as a new deafness gene. Homozygosity mapping followed by exome sequencing identified a 14.96 Mb locus on chromosome 4p15.32p15.1 containing a likely pathogenic missense variant in CLRN2 (c.494C > A, NM_001079827.2) segregating with the disease. Using in vitro RNA splicing analysis, we show that the CLRN2 c.494C > A variant leads to two events: (1) the substitution of a highly conserved threonine (uncharged amino acid) to lysine (charged amino acid) at position 165, p.(Thr165Lys), and (2) aberrant splicing, with the retention of intron 2 resulting in a stop codon after 26 additional amino acids, p.(Gly146Lysfs*26). Expression studies and phenotyping of newly produced zebrafish and mouse models deficient for clarin 2 further confirm that clarin 2, expressed in the inner ear hair cells, is essential for normal organization and maintenance of the auditory hair bundles, and for hearing function. Together, our findings identify CLRN2 as a new deafness gene, which will impact future diagnosis and treatment for deaf patients.

Identification of PP2A and S6 Kinase as Modifiers of Leucine-Rich Repeat Kinase-Induced Neurotoxicity - Joan Poh Ling Sim; Wang Ziyin; Adeline Henry Basil; Shuping Lin; Zhongcan Chen; Chengwu Zhang; Li Zeng; Yu Cai; Kah-Leong Lim (NeuroMolecular Medicine, 2020)
Mutations in LRRK2 are currently recognized as the most common monogenetic cause of Parkinsonism. The elevation of kinase activity of LRRK2 that frequently accompanies its mutations is widely thought to contribute to its toxicity. Accordingly, many groups have developed LRRK2-specific kinase inhibitors as a potential therapeutic strategy. Given that protein phosphorylation is a reversible event, we sought to elucidate the phosphatase(s) that can reverse LRRK2-mediated phosphorylation, with the view that targeting this phosphatase(s) may similarly be beneficial. Using an unbiased RNAi phosphatase screen conducted in a Drosophila LRRK2 model, we identified PP2A as a genetic modulator of LRRK2-induced neurotoxicity. Further, we also identified ribosomal S6 kinase (S6K), a target of PP2A, as a novel regulator of LRRK2 function. Finally, we showed that modulation of PP2A or S6K activities ameliorates LRRK2-associated disease phenotype in Drosophila .

Influence of canopy and topographic position on soil moisture response to rainfall in a hilly catchment of Three Gorges Reservoir Area, China - Muxing Liu; Qiuyue Wang; Li Guo; Jun Yi; Henry Lin; Qing Zhu; Bihang Fan; Hailin Zhang (Journal of Geographical Sciences, 2020)

Influence of Water Masses on the Biodiversity and Biogeography of Deep-Sea Benthic Ecosystems in the North Atlantic - Patricia Puerta; Clare Johnson; Marina Carreiro-Silva; Lea-Anne Henry; Ellen Kenchington; Telmo Morato; Georgios Kazanidis; José Luis Rueda; Javier Urra; Steve Ross; Chih-Lin Wei; José Manuel González-Irusta; et al. (Frontiers in Marine Science, 2020)

Climate‐induced changes in the suitable habitat of cold‐water corals and commercially important deep‐sea fishes in the North Atlantic - Telmo Morato; José‐Manuel González‐Irusta; Carlos Dominguez‐Carrió; Chih‐Lin Wei; Andrew Davies; Andrew K. Sweetman; Gerald H. Taranto; Lindsay Beazley; Ana García‐Alegre; Anthony Grehan; Pascal Laffargue; Francisco Javier Murillo; et al. (Global Change Biology, 2020)
The deep sea plays a critical role in global climate regulation through uptake and storage of heat and carbon dioxide. However, this regulating service causes warming, acidification and deoxygenation of deep waters, leading to decreased food availability at the seafloor. These changes and their projections are likely to affect productivity, biodiversity and distributions of deep‐sea fauna, thereby compromising key ecosystem services. Understanding how climate change can lead to shifts in deep‐sea species distributions is critically important in developing management measures. We used environmental niche modelling along with the best available species occurrence data and environmental parameters to model habitat suitability for key cold‐water coral and commercially important deep‐sea fish species under present‐day (1951–2000) environmental conditions and to project changes under severe, high emissions future (2081–2100) climate projections (RCP8.5 scenario) for the North Atlantic Ocean. Our models projected a decrease of 28%–100% in suitable habitat for cold‐water corals and a shift in suitable habitat for deep‐sea fishes of 2.0°–9.9° towards higher latitudes. The largest reductions in suitable habitat were projected for the scleractinian coral Lophelia pertusa and the octocoral Paragorgia arborea , with declines of at least 79% and 99% respectively. We projected the expansion of suitable habitat by 2100 only for the fishes Helicolenus dactylopterus and Sebastes mentella (20%–30%), mostly through northern latitudinal range expansion. Our results projected limited climate refugia locations in the North Atlantic by 2100 for scleractinian corals (30%–42% of present‐day suitable habitat), even smaller refugia locations for the octocorals Acanella arbuscula and Acanthogorgia armata (6%–14%), and almost no refugia for P. arborea . Our results emphasize the need to understand how anticipated climate change will affect the distribution of deep‐sea species including commercially important fishes and foundation species, and highlight the importance of identifying and preserving climate refugia for a range of area‐based planning and management tools.

Bismuth(III) interactions with Desulfovibrio desulfuricans: inhibition of cell energetics and nanocrystal formation of Bi2S3 and Bi0 - Larry L. Barton; Alex S. Granat; Seungyeol Lee; Huifang Xu; Nathaniel L. Ritz; Robert Hider; Henry C. Lin (BioMetals, 2019)

Spatial variation and soil nitrogen potential hotspots in a mixed land cover catchment on the Chinese Loess Plateau - Yun-long Yu; Zhao Jin; Henry Lin; Yun-qiang Wang; Ya-li Zhao; Guang-chen Chu; Jing Zhang; Yi Song; Han Zheng (Journal of Mountain Science, 2019)

Non-invasive estimation of root zone soil moisture from coarse root reflections in ground-penetrating radar images - Xinbo Liu; Xihong Cui; Li Guo; Jin Chen; Wentao Li; Dedi Yang; Xin Cao; Xuehong Chen; Qixin Liu; Henry Lin (Plant and Soil, 2019)

Correction to: Three dimensional characteristics of biopores and non-biopores in the subsoil respond differently to land use and fertilization - Zhongbin Zhang; Kailou Liu; Hu Zhou; Henry Lin; Daming Li; Xinhua Peng (Plant and Soil, 2018)

Reach and messages of the world's largest ivory burn - Alexander Braczkowski; Matthew H. Holden; Christopher O'Bryan; Chi‐Yeung Choi; Xiaojing Gan; Nicholas Beesley; Yufang Gao; James Allan; Peter Tyrrell; Daniel Stiles; Peadar Brehony; Revocatus Meney; et al. (Conservation Biology, 2018)
Recent increases in ivory poaching have depressed African elephant populations. Successful enforcement has led to ivory stockpiling. Stockpile destruction is becoming increasingly popular, and most destruction has occurred in the last 5 years. Ivory destruction is intended to send a strong message against ivory consumption, both in promoting a taboo on ivory use and catalyzing policy change. However, there has been no effort to establish the distribution and extent of media reporting on ivory destruction events globally. We analyzed media coverage of the largest ivory destruction event in history (Kenya, 30 April 2016) across 11 nation states connected to ivory trade. We used an online‐media crawling tool to search online media outlets and subjected 5 of the largest print newspapers (by circulation) in 5 nations of interest to content analysis. Most online news on the ivory burn came from the United States (81% of 1944 articles), whereas most of the print news articles came from Kenya (61% of 157 articles). Eighty‐six to 97% of all online articles reported the burn as a positive conservation action, whereas 4–50% discussed ivory burning as having a negative impact on elephant conservation. Most articles discussed law enforcement and trade bans as effective for elephant conservation. There was more relative search interest globally in the 2016 Kenyan ivory burn than any other burn in 5 years. Ours is the first attempt to track the reach of media coverage relative to an ivory burn and provides a case study in tracking the effects of a conservation‐marketing event.

Three dimensional characteristics of biopores and non-biopores in the subsoil respond differently to land use and fertilization - Zhongbin Zhang; Kailou Liu; Hu Zhou; Henry Lin; Daming Li; Xinhua Peng (Plant and Soil, 2018)

Modeling spring-summer phytoplankton bloom in Lake Michigan with and without riverine nutrient loading - Lin Luo; Jia Wang; Timothy Hunter; Dongxiao Wang; Henry A. Vanderploeg (Ocean Dynamics, 2017)

Microwave drying characteristics of microalgae (Chlorella vulgaris) for biofuel production - Al Rey C. Villagracia; Andres Philip Mayol; Aristotle T. Ubando; Jose Bienvenido Manuel M. Biona; Nelson B. Arboleda; Melanie Y. David; Roy B. Tumlos; Henry Lee; Ong Hui Lin; Rafael A. Espiritu; Alvin B. Culaba; Hideaki Kasai (Clean Technologies and Environmental Policy, 2016)

Bismuth(III) deferiprone effectively inhibits growth of Desulfovibrio desulfuricans ATCC 27774 - Larry L. Barton; Daniel A. Lyle; Nathaniel L. Ritz; Alex S. Granat; Ali N. Khurshid; Nada Kherbik; Robert Hider; Henry C. Lin (BioMetals, 2016)

Phosphorus amendment mitigates nitrogen addition-induced phosphorus limitation in two plant species in a desert steppe, China - Juying Huang; Hailong Yu; Henry Lin; Yu Zhang; Eric B. Searle; Zhiyou Yuan (Plant and Soil, 2016)

A record-breaking low ice cover over the Great Lakes during winter 2011/2012: combined effects of a strong positive NAO and La Niña - Xuezhi Bai; Jia Wang; Jay Austin; David J. Schwab; Raymond Assel; Anne Clites; John F. Bratton; Marie Colton; John Lenters; Brent Lofgren; Trudy Wohlleben; Sean Helfrich; et al. (Climate Dynamics, 2015)

Ground-penetrating radar-based automatic reconstruction of three-dimensional coarse root system architecture - Yuan Wu; Li Guo; Xihong Cui; Jin Chen; Xin Cao; Henry Lin (Plant and Soil, 2014)

Global reductions in seafloor biomass in response to climate change - Daniel O. B. Jones; Andrew Yool; Chih‐Lin Wei; Stephanie A. Henson; Henry A. Ruhl; Reg A. Watson; Marion Gehlen (Global Change Biology, 2014)

Forward simulation of root’s ground penetrating radar signal: simulator development and validation - Li Guo; Henry Lin; Bihang Fan; Xihong Cui; Jin Chen (Plant and Soil, 2013)

Impact of root water content on root biomass estimation using ground penetrating radar: evidence from forward simulations and field controlled experiments - Li Guo; Henry Lin; Bihang Fan; Xihong Cui; Jin Chen (Plant and Soil, 2013)

Application of ground penetrating radar for coarse root detection and quantification: a review - Li Guo; Jin Chen; Xihong Cui; Bihang Fan; Henry Lin (Plant and Soil, 2013)

Islands of Ice: Influence of Free-Drifting Antarctic Icebergs on Pelagic Marine Ecosystems - Maria Vernet; Kenneth Smith; Adrián Cefarelli; John Helly; Ronald Kaufmann; Hai Lin; David Long; Alison Murray; Bruce Robison; Henry Ruhl; Timothy Shaw; Alana Sherman; et al. (Oceanography, 2012)

Linking Carbon Saturation Concepts to Nitrogen Saturation and Retention - Michael J. Castellano; Jason P. Kaye; Henry Lin; John P. Schmidt (Ecosystems, 2012)

Subsurface flow processes in sloping cropland of purple soil - Jialilang Tang; Bo Zhu; Tao Wang; Xunqiang Cheng; Meirong Gao; Henry Lin (Journal of Mountain Science, 2012)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Suprachoroidal Drug Delivery to the Back of the Eye Using Hollow Microneedles - Samirkumar R. Patel; Angela S. P. Lin; Henry F. Edelhauser; Mark R. Prausnitz (Pharmaceutical Research, 2011)

Hydrological and biogeochemical controls on the timing and magnitude of nitrous oxide flux across an agricultural landscape - MICHAEL J. CASTELLANO; JOHN P. SCHMIDT; JASON P. KAYE; CHARLES WALKER; CHRIS B. GRAHAM; HENRY LIN; CURTIS J. DELL (Global Change Biology, 2010)
Anticipated increases in precipitation intensity due to climate change may affect hydrological controls on soil N 2 O fluxes, resulting in a feedback between climate change and soil greenhouse gas emissions. We evaluated soil hydrologic controls on N 2 O emissions during experimental water table fluctuations in large, intact soil columns amended with 100 kg ha −1 KNO 3 ‐N. Soil columns were collected from three landscape positions that vary in hydrological and biogeochemical properties ( N = 12 columns). We flooded columns from bottom to surface to simulate water table fluctuations that are typical for this site, and expected to increase given future climate change scenarios. After the soil was saturated to the surface, we allowed the columns to drain freely while monitoring volumetric soil water content, matric potential and N 2 O emissions over 96 h. Across all landscape positions and replicate soil columns, there was a positive linear relationship between total soil N and the log of cumulative N 2 O emissions ( r 2 = 0.47; P = 0.013). Within individual soil columns, N 2 O flux was a Gaussian function of water‐filled pore space (WFPS) during drainage (mean r 2 = 0.90). However, instantaneous maximum N 2 O flux rates did not occur at a consistent WFPS, ranging from 63% to 98% WFPS across landscape positions and replicate soil columns. In contrast, instantaneous maximum N 2 O flux rates occurred within a narrow range (−1.88 to −4.48 kPa) of soil matric potential that approximated field capacity. The relatively consistent relationship between maximum N 2 O flux rates and matric potential indicates that water filled pore size is an important factor affecting soil N 2 O fluxes. These data demonstrate that matric potential is the strongest predictor of the timing of N 2 O fluxes across soils that differ in texture, structure and bulk density.

Analysis of Acropora muricata Calmodulin (CaM) Indicates That Scleractinian Corals Possess the Ancestral Exon/Intron Organization of the Eumetazoan CaM Gene - Chih-Yung Chiou; I-Ping Chen; Chienhsun Chen; Henry Ju-Lin Wu; Nuwei Vivian Wei; Carden C. Wallace; Chaolun Allen Chen (Journal of Molecular Evolution, 2008)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Localization of the genes encoding the type I diabetes autoantigens, protein-tyrosine phosphatases IA2 and IAR - Grant Morahan; Dexing Huang; Wei-Ping Yu; Lin Cui; Henry DeAizpurua; Catherine J. Pallen (Mammalian Genome, 1998)